Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Nur Haslinda; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
AbstractThis research is conducted to examine the effect of firm size, leverage and profitability on the firm value in banking campanies listed on the Indonesia stock exchange in 2015-2017.The population used in this study is the banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2016. The sampling method is puposive sampling according to predetermined criteria. The number of samples is 30 companies. The data in this study used multiple linear regression, classical assumptions and hyphotesis testing.The result of this study indicate that firm size has negative significant effect on firm value, leverage has positive and insignificant effect on firm value and profitability has positive significant effect on firm value. Keywords: Firm Size, Leverage, Profitability, Firm Value